Tholeiitic to calc-alkaline and alkaline volcanisms in an extensional arc setting of a Tethyan ophiolite: insights from small-scale compositional and temporal transitions from the Dali sector (Armenia). (January 2023) - Seyler, Monique; Galoyan, Ghazar; Witt, César; Danelian, Taniel
Highlights: Dali's sector shows a transition from island-arc magmatism to more alkaline volcanism. Alkaline lavas comprise E-MORB, transitional calc-alkaline basalts and atypical OIB. The transition to alkaline lavas occurred in the Tithonian–Valanginian time interval. The diversity of magmatic affinities suggests an extensional oceanic arc setting. Abstract: New field and petrographic observations, combined with whole rock and mineral geochemical analyses are applied on volcanic rocks present in the Dali sector, east of Lake Sevan (Armenia). A small-scale sampling of the volcanic sequence allows us to identify, for the first time in Armenian ophiolites, two groups of lavas (groups B and C1) stratigraphically and geochemically intermediate between previously recognized arc tholeiite (group A) and OIB-like (group C2) basalts. Their age is constrained by two distinct intercalated radiolarite sequences, which were dated as Tithonian – Valanginian. Group B lavas are low-K tholeiitic basalts and basaltic andesites derived from an enriched mantle source (LaN /YbN 1.8–6.1; SmN /YbN 1.3–2.4; Nb/Yb 2.0–6.7). The composition of their clinopyroxenes ranges from Ti-poor augite to Ti-rich diopside augite in correlation with higher La/Yb and Nb/Yb ratios in bulk rocks. Group C1 lavas are basaltic andesites containing Ti and Na-rich amphiboles (kaersutite, hastingsite) as major mineral phases. Three analyzed diopside-amphibole-porphyritic samples are alkaline trachybasalts (LaN /YbN 20–21; Nb/Yb 16–18). Both the group B and C1 lavas exhibit variable, although moderate, enrichments in Th/Yb for given Nb/Yb ratios and Nb negative anomalies in normalized multi-elements patterns (Nb/La 0.53–1.02), which are not correlated with the degree of enrichment of their mantle sources. Our results suggest that transitional and OIB-like volcanic lavas were generated by low- (group B) and very low- (groups C1–C2) melting of a heterogeneous mantle source in an oceanic arc–back-arc system in extension, possibly in relation with slab break-off.